Climate change effect on the characteristics of raw domestic wastewater, sedimentation pond water, and treated wastewater - Ashraf O. Khashroum (Tikrit Journal for Agricultural Sciences, 2024)
The objective of this work was to investigate the effect of climate change on the characteristics of raw domestic wastewater, sedimentation pond water, and treated wastewater. The wastewater samples were collected from Khirbet Assamra wastewater treatment plant (KSWTP) in Azzarga Governorate in the Middle Region of Jordan. Descriptive statistics and inferential statistical tests were used for describtion and comparison purposes. Statistical analysis aimed at evaluating the ability of the sedimentation process to purify the water and assessing the overall wastewater treatment efficiciency of KSWTP. The results of the analysis showed that there are significant differences between the raw domestic wastewater, sedimentation pond water, and treated wastewater in pH (F = 15.486, df = 149, p = .000), the chemical oxygen demand (F = 2486.459, df = 149, p = .000), biochemical oxygen demand (F = 2298.142, df = 149, p = .000), ammonium ion concentration (F = 4645.039, df = 149, p = .000), total Kjeldahl nitrogen concentration (F = 5908.067, df = 149, p = .000), and the concentration of the total suspended solids (F = 715,376, df = 149, p = .000). When the characteristics of the raw domestic wastewater were compared with the characteristics of the treated wastewater, it was found that the wastewater treatment reduced the concentrations of total phosphorous and oil and grease and the counts of faecal coliform bacteria but had no significant effect on the mean water temperature and the concentration of dissolved phosphorous. It can be concluded that domestic wastewater treatment in KSWTP was to a large extent efficient in reducing the concentrations of total phosphorous and oil and grease and the counts of the faecal coliform bacteria in the treated wastewater. Further research is needed to compare levels of performance of other wastewater treatment methods with the method applied in KSWTP